Analysis of Surgical Freedom Variation Across the Basilar Artery Bifurcation: Towards a Deeper Insight Into Approach Selection for Basilar Apex Aneurysms. Issue 6 (3rd March 2018) - Tayebi Meybodi, Ali; Benet, Arnau; Rodriguez Rubio, Roberto; Yousef, Sonia; Lawton, Michael T
Abstract: BACKGROUND: The orbitozygomatic approach is generally advocated over the pterional approach for basilar apex aneurysms. However, the impact of the extensions of the pterional approach on the obtained maneuverability over multiple vascular targets (relevant to basilar apex surgery) has not been studied before. OBJECTIVE: To analyze the patterns of surgical freedom change across the basilar bifurcation between the pterional, orbitopterional, and orbitozygomatic approaches. METHODS: Surgical freedom was assessed for 3 vascular targets important in basilar apex aneurysm surgery (ipsilateral and contralateral P1-P2 junctions, and basilar apex), and compared between the pterional, orbitopterional, and orbitozygomatic approaches in 10 cadaveric specimens. RESULTS: Transitioning from the pterional to orbitopterional approach, the surgical freedom increased significantly at all 3 targets ( P  < .05). However, the gain in surgical freedom declined progressively from the most superficial target (60% for ipsilateral P1-P2 junction) to the deepest target (35% for contralateral P1-P2 junction). Conversely, transitioning from the orbitopterional to the orbitozygomatic approach, the gain in surgical freedom was minimal for the ipsilateral P1-P2 and basilar apex (<4%), but increased dramatically to 19% at the contralateral P1-P2 junction. CONCLUSION: The orbitopterional approach provides a remarkable increase in surgical maneuverability compared to the pterional approach for the basilar apex target and the relevant adjacent arterial targets. However, compared to the orbitopterional, the orbitozygomatic approach adds little maneuverability except for the deepest target (ie, contralateral P1-P2 junction). Therefore, the orbitozygomatic approach may be most efficacious with larger basilar apex aneurysms limiting the control over of the contralateral P1 PCA.